1987
DOI: 10.1002/ajh.2830240202
|View full text |Cite
|
Sign up to set email alerts
|

Role of immune stimulation in the etiology of multiple myeloma: A case control study

Abstract: A hospital-based case-control study of 153 multiple myeloma (MM) cases and 459 controls was conducted to evaluate the hypothesis that chronic or frequent infections or allergic and autoimmune diseases might be of higher prevalence in individuals who develop MM. Information was obtained by direct interviews of subjects. Controls were matched to cases on age, sex, race, and hospital. "Immune-stimulating conditions" included chronic infections such as pyelonephritis, urinary tract infections (UTIs), prostatitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Findings for allergic conditions are inconsistent and do not support a causal relationship, as several studies have reported associations below, 24,47,87,[279][280][281] while others have reported associations above the null. 46,83,131,202,[282][283][284] Pearce et al 83 reported a marginally significant positive association (OR 5 1.9, 95% CI: 1.0-3.5) of multiple myeloma with hay fever, a finding not replicated by others.…”
Section: Immune Function and Medical Historymentioning
confidence: 81%
See 2 more Smart Citations
“…Findings for allergic conditions are inconsistent and do not support a causal relationship, as several studies have reported associations below, 24,47,87,[279][280][281] while others have reported associations above the null. 46,83,131,202,[282][283][284] Pearce et al 83 reported a marginally significant positive association (OR 5 1.9, 95% CI: 1.0-3.5) of multiple myeloma with hay fever, a finding not replicated by others.…”
Section: Immune Function and Medical Historymentioning
confidence: 81%
“…Some studies have reported increased risk among patients with a history of rheumatoid arthritis, 24,83,202,[290][291][292] while others have reported relative risks below 1.0. 87,280,281,289,[293][294][295] The largest case-control studies that evaluated rheumatoid arthritis all reported nonsignificant relative risks below 1.0. 87,280,281,293 In particular, Lewis et al In an Australian cohort study, risk of multiple myeloma was significantly elevated (SIR 5 12.1, 95% CI: 2.50-35.4; 3 observed cases) among persons with AIDS.…”
Section: Immune Function and Medical Historymentioning
confidence: 99%
See 1 more Smart Citation
“…role of occupational exposure [ 1,2,4,8,9], and of chronic antigenic stimulation [ 1,2,5,10] in multiple myeloma, using the case-control method, this is the first study to consider these risk factors in MGUS. Despite the limitations of case-control studies [6], the observation of significant associations with some occupational exposure and with overall chronic antigenic stimulation suggests that these factors may play an important role in inducing MGUS.…”
Section: Patients Controls and Methodsmentioning
confidence: 99%
“…For those studies in which the risk measurement was not calculated but where sufficient data were presented, a fixed effects model was used to calculate the unadjusted RR (22)(23)(24)(25). For those studies meeting the inclusion criteria but which reported unadjusted risk measurements, RR, OR, and SIRs were extracted (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%